PENDEKATAN NARATIF DALAM PRAKTIK PEKERJAAN SOSIAL UNTUK MENGATASI TRAUMA KEKERASAN DALAM RUMAH TANGGA - br. Sitepu, Badikenita (Istek Widuri Jakarta, 2024)
The narrative approach in social work practice is an effective intervention strategy to help victims of domestic violence (DV) recover their identity and rebuild their meaning after experiencing trauma. This study aims to analyze the application of the narrative approach in the context of social work as an effort to recover from trauma caused by domestic violence. This approach starts from the assumption that a person's life experience is constructed through narratives or stories told about themselves and their environment. Through the process of